TYPES OF MEDICO-LEGAL CASES REPORTED AT THE CASUALTY DEPARTMENT OF AYUB TEACHING HOSPITAL ABBOTTABAD - Jadoon, Omair Khan; Shireen, Fatima; Seema, Nighat; Afzal, Ejaz; Ahmad, Iftikhar; Irshad, Romana; Sattar, Hamza (Journal of Ayub Medical College Abbottabad, 2020)
Background: Medicolegal data is very important for administrators, health officials, philanthropists, social workers, law enforcement agencies. Because it is used for planning and implementation of strategies in order to reduce further incidents. This study is conducted with the aim to determine different types of medicolegal cases and patterns of weapons used. Methods: A total of 246 cases were studied from 1st September 2017 to 31st January 2018. All information was collected on a pro forma. Statistical analysis was done by MS Excel. Results: Out of 246 cases, 219 were male and 27 were female with age ranging from 3 to 72 years. Among total, 162(65.85%) patients were injured due to blunt weapon, 17 (6.91%) cases of firearms, 23 (9.34%) in road traffic accidents, 15 (6.09%) sharp-edged weapons, 7 (2.84%) cases were of sexual violence, 11 (4.47%) were of poisoning. Conclusion: Injuries of blunt weapons followed by sharp edge and accidental cases occurred more frequently. Keywords: Medico-Legal Case' Injury; Road Traffic Accidents; Physical Assault; Poisoning